2015
DOI: 10.1038/srep18133
|View full text |Cite
|
Sign up to set email alerts
|

A novel single-chain antibody redirects adenovirus to IL13Rα2-expressing brain tumors

Abstract: The generation of a targeting agent that strictly binds to IL13Rα2 will significantly expand the therapeutic potential for the treatment of IL13Rα2-expressing cancers. In order to fulfill this goal, we generated a single-chain antibody (scFv47) from our parental IL13Rα2 monoclonal antibody and tested its binding properties. Furthermore, to demonstrate the potential therapeutic applicability of scFv47, we engineered an adenovirus by incorporating scFv47 as the targeting moiety in the viral fiber and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…RNA sequencing analysis detected CDH2 (encoding N-Cadherin) expressed at significantly higher levels in iSOX11 cells grown in 2D and as spheroids, whilst other EMT markers, including CDH1 (encoding E-cadherin) and VIM were not significantly changed compared to control cells ( Supplementary file 1 ). Other notable downstream targets of SOX11 included MEX3A , which encodes an RNA-binding protein, that marks slowly proliferating multipotent stem cells in mouse intestine ( Barriga et al, 2017 ) and totipotent cells in C. elegans ( Pereira et al, 2013 ); MMP11, ST6GALNAC5, and TUBB3, which are highly expressed in breast cancers that metastasize to brain ( Bos et al, 2009 ; Kim et al, 2015 ; Lee et al, 2016 ). We confirmed that a number of putative SOX11 targets of interest ( Figure 3C and Figure 3—figure supplement 1 , Supplementary file 2 ), including MEX3A and TUBB3 were upregulated in iSOX11 cells when measured by qPCR ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…RNA sequencing analysis detected CDH2 (encoding N-Cadherin) expressed at significantly higher levels in iSOX11 cells grown in 2D and as spheroids, whilst other EMT markers, including CDH1 (encoding E-cadherin) and VIM were not significantly changed compared to control cells ( Supplementary file 1 ). Other notable downstream targets of SOX11 included MEX3A , which encodes an RNA-binding protein, that marks slowly proliferating multipotent stem cells in mouse intestine ( Barriga et al, 2017 ) and totipotent cells in C. elegans ( Pereira et al, 2013 ); MMP11, ST6GALNAC5, and TUBB3, which are highly expressed in breast cancers that metastasize to brain ( Bos et al, 2009 ; Kim et al, 2015 ; Lee et al, 2016 ). We confirmed that a number of putative SOX11 targets of interest ( Figure 3C and Figure 3—figure supplement 1 , Supplementary file 2 ), including MEX3A and TUBB3 were upregulated in iSOX11 cells when measured by qPCR ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…7,8 To selectively target IL13Rα2, we previously had generated a monoclonal antibody (MAb) and scFv that specifically recognized IL13Rα2 (clone 47; scFv47) with a high affinity and no cross-reactivity to IL13Rα1. 23,24 Here, we report the development of IL13Rα2-specific CARs with a scFv47-based antigenbinding domain (IL13Rα2-CARs). We show that IL13Rα2-CARs require a short spacer region for optimal functionality, and that IL13Rα2-CAR T cells are able to recognize and kill only IL13Rα2positive and not IL13Rα1-positive target cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…For intracranial glioma xenograft implantation, GL261-OVA (4 × 10 5 cells) murine glioma cells were implanted via cranial guide screws as described previously. 36 Mice were cared for in accordance with a study-specific animal protocol approved by Northwestern University Institutional Animal Care and Use Committee. Five days after tumor implantation, mice were randomly separated into three groups and were then injected with either 2.5 μL PBS or 10 9 VPs.…”
Section: Methodsmentioning
confidence: 99%